Characteristic mechanism for fast H− conduction in LaH2.5O0.25. (15th May 2022) - Iskandarov, Albert; Tada, Tomofumi; Iimura, Soshi; Hosono, Hideo
Graphical abstract: Abstract: Solid hydrides are a new class of ionic conductors promising for future applications for hydrogen-carrier, catalysis, and energy conversion. The record-high H − conductivity reported for LaH 2.5 O 0.25 is caused by extraordinarily large pre-exponential factor, which cannot be justified within any simple diffusion picture. To reveal H − dynamics in LaH 2.5 O 0.25 on atomistic level, we developed DFT-based neural-network-potential for large-scale molecular dynamics (MD) simulation and discovered the H − diffusion mechanism: the stoichiometric vacancies are ordered and almost immobile, but they can be rarely kicked-out and become fast mobile vacancies that migrate in a coupled manner with 3 H − ring-like rotations. The MD and DFT phonon analysis reveal that the mobile vacancy formation gives rise to an extremely large entropy leading to the anomalously large pre-exponential factor, and that the anharmonicity of H − vibrations causes the large pre-exponential factor. A design concept for faster H − conductor is proposed based on the present finding.